Esther and Purim - LEE, Lydia (Journal of Research for Christianity in China (JRCC), 2022)
The history of every Jewish festival mentioned in the Hebrew Bible is found within the Pentateuch, except Purim, the establishment of which is recorded in one of the Megilloth, the Book of Esther. This article illustrates the secondary nature of MT Esther 9:20–32 within the book, before outlining various arguments for its pagan origin. In addition, with the help of several primary sources, such as the Second Book of Maccabees, the colophon of Septuagint Esther, and the rabbinic sources, we conclude that Purim has become one of the most important Jewish festival since the Hellenistic Period. Throughout the centuries, when the Jews were living under foreign rules, the topsy-turvy exhilaration accompanied by the celebration of Purim gave rare chances for the marginalized Jews to unleash their suppressed hope and desire.
Keywords: Book of Esther, Purim, Hebrew Bible, Hellenistic Period, Jewish Festivals